Altered brain network integrity after childhood maltreatment: A structural connectomic DTI‐study. Issue 2 (24th October 2016) - Puetz, V.B.; Parker, D.; Kohn, N.; Dahmen, B.; Verma, R.; Konrad, K.
Abstract: Childhood maltreatment is associated with alterations in neural architecture that potentially put these children at increased risk for psychopathology. Alterations in white matter (WM) tracts have been reported, however no study to date has investigated WM connectivity in brain networks in maltreated children to quantify global and local abnormalities through graph theoretical analyses of DTI data. We aimed for a multilevel investigation examining the DTI‐based structural connectome and its associations with basal cortisol levels of 25 children with documented maltreatment experiences before age 3, and 24 matched controls (age: 10.6 ± 1.75 years). On the global and lobar level, maltreated children showed significant reductions in global connectivity strength, local connectivity and increased path length, suggesting deviations from the small‐world network architecture previously associated with psychopathology. Reductions in global connectivity were associated with placement instability, attenuated cortisol secretion and higher levels of internalizing and externalizing behaviours. Regional measures revealed lower connectivity strength especially in regions within the ventromedial prefrontal cortex (vMPFC) in maltreated children. These findings show that childhood maltreatment is associated with systemic global neurodevelopmental alterations in WM networks next to regional alterations in areas involved in the regulation of affect. These alterations in WM organization could underlie global functional deficits and multi‐symptom patterns frequently observed in children with maltreatment experiences. Hum Brain Mapp 38:855–868, 2017 . ©2016 Wiley Periodicals, Inc.